Tempo das carnes no Siará Grande: dinâmica social, produção e comércio de carnes secas na Vila de Santa Cruz do Aracati (c.1690-c.1802). - Rolim, Leonardo Cândido (2012)
This study has as the main analysis focus the social dynamics of Santa Cruz do Aracati village, Siará Grande captaincy, during the production and commercialization of jerked meat in the XVIII century. We perform a conjunctural examination of the captaincies hinterlands situated on the north of Brazil State, working with the conquest basis: the conjuncture on Pernambuco captaincy in the XVII century second half, the land distribution and the pastoral activity. Being the jerked meat a fundamental product in matters of internal supply and, during a lot of time, essential to maintain the dynamics of locals and regionals routes, we investigate how this gender production and commercialization had established in the Aracati village and, mainly, how it projected itself as an important hinterland s port in the north captaincies. We still analyze the violence cases, crimes, murders and thefts occured in the village mainly during the called meats age , besides of trying to investigate how the free workers and slaves organize themselves in the jerked meat manufacture process. And, at last, we scrutinize the commercial dynamics of the village, trying to recompose the mercantile routes and connections developed in the XVIII century second half, also paying attention to the jerked meat consumption on the Portuguese America subject.